The Influence of Temperature and Irradiance on Performance of the photovoltaic panel in the Middle of Iraq - Moafaq Kaseim Al-Ghezi; Roshen Tariq Ahmed; Miqdam Tariq Chaichan (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
The photovoltaic (PV) panels are expected to be the most important systems to meet global energy demand by converting solar energy into electricity. The main obstacle to the widespread deployment of the PV systems its the limited efficiency, which are greatly affected by the solar radiation and the operating temperature. The full knowledge of the performance, efficiency and output power of photovoltaic modules and the extent of their change with the fluctuations of solar radiation and temperature is necessary to determine the optimal size of the system and avoid the financial risks of the project. This paper investigated numaricaly and experimentaly the influence of operating temperature and solar radiation on the output power and efficiency of polycrystalline PV panels in Baghdad-Iraq. The PVsyst software was used to simulate a model implementing simulation results presented the impact of variations temperature and solar radiation in the curves of I-V, P-V and efficiency. In order to verify the reliability of the simulated results with experimental ones, several measuring devices have been used to conduct field experiments in the outdoor conditions. It were used to determine the characteristics and performance of a 120W polycrystalline PV panel for different ranges of solar radiation and operating temperature. The simulation results showed that the current, voltage, output power and efficiency increased with increasing solar radiation, while they decreased with increasing temperature except the current that was increased. The experimental and simulated results were identical in terms of the effect of temperature and solar radiation on the current, voltage, output power and efficiency of the PV panel. The experimental tests showed that when the temperature is increased by 1°C, the current was increased by about 0.068%, the voltage decreased by 0.34%, the output power decreased by 0.489% and the efficiency decreased about 0.586%. The experimental results displayed that the parameters of the PV panel under real operating conditions behave differently than in the standard test conditions (STC), as they are strongly affected by weather fluctuations in terms of temperature and solar radiation